Bilateral Epididymal Cyst in 14 year-old Boy: a case report (Journal of Health Sciences, 2014)
Bilateral epididymal cysts are rare in childhood. Clinically they may present as acute scrotum and should be differentiated from other pathologies. Here in, we report bilateral epididymal cysts in a 14-year-old boy. He was admitted to emergency department with symptoms of acute left scrotum. There was no history of trauma or infection. Blood analyses, including testis tumor markers were unremarkable. Bilateral epididymal cysts were diagnosed on ultrasonography evaluation. Medical treatment did not stop his scrotal pain. During scrotal exploration, there was no evidence of testicular torsion or any other pathology. An excision of cyst was performed. Histopathologically, the cyst wall was lined by columnar epithelia. As a result of these findings, a pathological diagnosis of epididymal cyst was made. The synchronized evaluation of clinical and ultrasonography findings with an appropriate histopathological evaluation can usually diagnose this rare pathology.